Financialisation in the European Periphery and the Sovereign Debt Crisis: The Portuguese Case - Barradas, R.; Lagoa, S.; Leão, E.; Mamede, R.P. (Dinâmia’CET-IUL Working Paper Nº 2015/12, 2015)
The financial sector has acquired great prominence in most developed economies. However, some authors argue that the growth of finance is at the root of the current financial and economic difficulties. This paper aims to analyse this claim by looking at financialisation in the European periphery, focusing on the Portuguese case. The emergence of this phenomenon is contextualised from a historical, economic and international perspective. Based on the analysis of several indicators, the paper concludes that the Portuguese economy exhibits symptoms of financialisation, and that this has not only revealed the structural weaknesses of the Portuguese economy but also played an important role in the emergence of the recent Portuguese sovereign debt crisis.